1997
DOI: 10.1021/ja9717673
|View full text |Cite
|
Sign up to set email alerts
|

Cu K-Edge XAS Study of the [Cu2(μ-O)2] Core:  Direct Experimental Evidence for the Presence of Cu(III)

Abstract: Copper in its infrequently observed Cu(III) oxidation state has gained attention recently, in particular as a proposed constituent of O 2 -cleaving binuclear and trinuclear complexes. 1,2 A few discrete molecular species generally accepted as containing Cu(III) are known. 3 Assignment of the formal Cu(III) oxidation state in these compounds is based on a variety of spectroscopic, electrochemical, and structural evidence. In particular, their very short Cu-ligand bond distances relative to bond lengths in thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

20
125
1
1

Year Published

1999
1999
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(147 citation statements)
references
References 22 publications
20
125
1
1
Order By: Relevance
“…The Cu K-edge energy in 2 is about 0.7 eV higher than that in 1 in accord with a metal-centered one-electron oxidation of 1 to 2. [8] Furthermore, the analysis of the Co and Cu K-edge EXAFS spectra (extended X-ray absorption fine structure) of 1 and 2 shows that oxidation of 1 to 2 does not affect the Co ± N and Co ± S bond lengths (2.02(1) and 2.239(6) , respectively); they are in excellent agreement with the crystallographically determined values for 1-(BPh 4 ) 2´6 CH 3 CN. Even the Cu ± S distances in 1 and 2 appear to be identical (but see the comment in ref.…”
Section: Methodssupporting
confidence: 73%
See 1 more Smart Citation
“…The Cu K-edge energy in 2 is about 0.7 eV higher than that in 1 in accord with a metal-centered one-electron oxidation of 1 to 2. [8] Furthermore, the analysis of the Co and Cu K-edge EXAFS spectra (extended X-ray absorption fine structure) of 1 and 2 shows that oxidation of 1 to 2 does not affect the Co ± N and Co ± S bond lengths (2.02(1) and 2.239(6) , respectively); they are in excellent agreement with the crystallographically determined values for 1-(BPh 4 ) 2´6 CH 3 CN. Even the Cu ± S distances in 1 and 2 appear to be identical (but see the comment in ref.…”
Section: Methodssupporting
confidence: 73%
“…In contrast, the spectrum of 2 is typical for a triplet ground state (S 1) with small zero-field splitting. In summary, we have shown that six bridging thiolato ligands are capable of stabilizing a high-spin d 8 (%): C 52.2, H 6.1, N 4.7, S 10.7, Co 6.6, Cu 3.5; found: C 51.9, H 6.1, N 4.5, S 10.9, Co 6.5, Cu 3.5.…”
Section: Methodsmentioning
confidence: 79%
“…Avery weak preedge peak is detected at 8980.5 eV,w hile am ore intense feature is observed in the edge at 8986.5 eV.W hereas the position of the first 1s!3d transition is an unambiguous diagnostic of Cu III ,t he more intense 1s!4p + LMCT shakedown transition is more ligand-dependent and can only support the conclusion drawn from the weak quadrupole transition. [17] Thec yclic voltammograms and the differential pulse voltammograms of complexes 1, 2,a nd 3 were measured in CH 2 Cl 2 /0.1m TBAP (see Figure S1 and Table S2). Each of the three copper complexes displayed one reversible oxidation and one reversible reduction step.T he oxidation couple was (2), and À0.64(90) (3)v ersus ferrocene/ferrocenium.…”
Section: Introductionmentioning
confidence: 99%
“…Cu K-edge XANES were generally characterized by two peaks along the rising maximum edge, namely the 1s  4p main transition along with a 1s  (4p+shakedown) transition, assigned as the 1s  4p transition with concurrent ligand to metal charge transfer (LMCT), as illustrated in Figure 2A and S14. 8 The XANES spectrum of 2 -relative to 2 2-shows a clear edge energy shift of 1.5 eV at around half height and 0.65 normalized absorption, reflecting the higher ionization energy required for ejecting a core 1s electron from a more positively charged ion. The distinct metal-centered oxidation of 2 -vs. 2 2-is shown by the 1.5 eV energy shift in the pre-edge energy range from 8979.4 to 8980.9 eV, corresponding to the 1s  3d electronic transition ( Figure 2A, S16, Table S1).…”
mentioning
confidence: 97%